2012
DOI: 10.1136/bmjopen-2012-002089
|View full text |Cite
|
Sign up to set email alerts
|

Dying to be famous: retrospective cohort study of rock and pop star mortality and its association with adverse childhood experiences

Abstract: ObjectivesRock and pop fame is associated with risk taking, substance use and premature mortality. We examine relationships between fame and premature mortality and test how such relationships vary with type of performer (eg, solo or band member) and nationality and whether cause of death is linked with prefame (adverse childhood) experiences.DesignA retrospective cohort analysis based on biographical data. An actuarial methodology compares postfame mortality to matched general populations. Cox survival and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…4, but it is striking how those under the age of 35 identified higher levels of anxiety, depression and 'other' compared to those over 35. These findings chime to a certain extent with those of Bellis et al (2012) and Kenny and Asher (2016) whose work suggested that mortality rates decreased in those over the age of 25. What does this all tell us?…”
Section: A Deep Dive: Solo Artists Gender and Agesupporting
confidence: 66%
See 1 more Smart Citation
“…4, but it is striking how those under the age of 35 identified higher levels of anxiety, depression and 'other' compared to those over 35. These findings chime to a certain extent with those of Bellis et al (2012) and Kenny and Asher (2016) whose work suggested that mortality rates decreased in those over the age of 25. What does this all tell us?…”
Section: A Deep Dive: Solo Artists Gender and Agesupporting
confidence: 66%
“…It is in this environment that we have seen in recent years increasing talk of 'resilience' (Newsinger and Serafini, 2019) -a highly loaded term which we will return to at the end of the book. In the context of findings which suggest that musicians suffer from high levels of anxiety and depression, it is interesting how much attention is paid to the possibility that this group may contain a larger portion of people who have suffered, for example, early childhood trauma (Bellis et al, 2012). It is equally interesting how neurosciences consider that biological and neurological factors might be responsible for elements of music perception and performance (Marin and Perry, 1999), and that by extension musician's brains might be somehow different to those of non-musicians (Gaser and Schlaug, 2003;Schlaug, 2011), perhaps making them more susceptible to emotional distress.…”
Section: Music and Suffering: The Limits Of Magical Thinkingmentioning
confidence: 99%
“…Less research has explored the causal direction of this effect. Some evidence points to social isolation as an outcome of substance use (e.g., Link et al, 1997 ; Vangeest and Johnson, 2002 ), whereas other studies suggest social isolation has a causal role in the development of SUD (e.g., Bellis et al, 2012 ; Wakefield et al, 2015 ). It is possible that both pathways may be at work, but apply to different sub-populations of individuals with SUDs.…”
Section: Introductionmentioning
confidence: 99%
“…Drug-related deaths occur regularly and attract significant media coverage [2]. It was shown, that rock/pop star mortality increases relative to the general population with time since fame [3]. In professional musical performance artists, performance-related musculoskeletal pain is a common disorder and is associated with depression and music performance anxiety [4].…”
Section: Introductionmentioning
confidence: 99%